Real-Life Experiences of Herpes Simplex Virus Type 2 Genital Herpes in the United States: A Structured Literature Review and Qualitative Concept Elicitation Study - Eliazar Sabater Cabrera; Claire Trennery; Amy M. Jones; Natasha Griffiths; Elizabeth Foley; Matthew M. Hamill; Magdalena Schwarz (Infectious Diseases and Therapy)
Abstract Introduction Research on real-life experiences of herpes simplex virus type 2 (HSV-2) genital herpes (GH) is scarce. This study primarily aimed to characterize the signs/symptoms and impacts of Ý (HRQoL) of people living with HSV-2 GH in the United States. The secondary aim was to map the identified signs/symptoms and impact concepts onto existing patient-reported outcome (PRO) measures to assess PRO coverage. Methods A structured literature review and concept elicitation (CE) interviews were conducted based on predefined eligibility criteria. The literature search was conducted across three digital databases and publicly available online resources. The CE interviews were conducted among three participant groups with a confirmed HSV-2 GH diagnosis. A conceptual model was developed based on signs/symptoms and HRQoL impact concepts, identified from the literature review and CE interviews. Key concepts from the model were mapped onto three existing PRO instruments [Herpes Symptoms Checklist (HSC), Herpes Outbreak Impact Questionnaire (HOIQ), and Recurrent Genital Herpes Quality of Life questionnaire (RGHQoL)] to assess concept coverage. Results Overall, 26 records were included in the literature review and 30 participants were recruited for CE interviews. The final conceptual model included 35 signs/symptoms and 59 impact concepts categorized among 6 and 9 domains, respectively. Most frequently reported signs/symptoms were itching, sores/lesions/blisters, and body pain. Sores/lesions/blisters were reported as most bothersome. Most frequently reported impact concepts were anxiety and worry, concerns about disclosing diagnosis, and loss of self-esteem/confidence. Conceptual mapping revealed that, when used together, existing PRO instruments provided comprehensive coverage of most concepts (HSC 83%, HOIQ 56%, and RGHQoL 50% of domains covered, respectively). Conclusions Participants experienced a range of signs/symptoms and HRQoL impacts. Existing PRO measures provided comprehensive coverage of recurrent HSV-2 GH specific concepts for the domains they measured. Graphical Plain Language Summary